2008
DOI: 10.1039/b809245a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high quality p-type Zn3P2 nanowires and their application in MISFETs

Abstract: Single-crystalline Zn 3 P 2 nanowires (NWs) have been synthesized on silicon (Si) substrates via a vapor phase transport method. Zn (99.99%) powder and InP (99.99%) fragments were used as the sources, and 10 nm thick thermal evaporated gold (Au) film was used as the catalyst. The as-prepared Zn 3 P 2 NWs have diameters of 100-200 nm and lengths of more than 10 mm. Single NW metalinsulator-semiconductor field-effect transistors (MISFETs) based on Zn 3 P 2 NWs were fabricated. Electrical transport measurements s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…10 Although the Co 2 P phase (2θ=40.8, 43.4, 44.2 and 52.1 o , indexing respectively to (121), (211), (130) and (002) planes) appeared to be good quality at above 600 o C, the Co 3 (PO 4 ) 2 species (see Fig. 3 in detail) can not be reduced until the temperature reached 700 o C. The XRD result indicated that 15 phase-pure Co 2 P can be obtained at temperatures of above 700 o C. For the sake of comparison, Table 1 summarizes the phase structures of the samples obtained in this study. It was clear from Table 1 that pure MoP and Co 2 P can be obtained by 25 reduction of their corresponding precursors in DME at above 700 o C. In the case of Ni phosphide, reduction temperature was the key factor in the synthesis.…”
Section: Sample Characterizationsmentioning
confidence: 94%
See 4 more Smart Citations
“…10 Although the Co 2 P phase (2θ=40.8, 43.4, 44.2 and 52.1 o , indexing respectively to (121), (211), (130) and (002) planes) appeared to be good quality at above 600 o C, the Co 3 (PO 4 ) 2 species (see Fig. 3 in detail) can not be reduced until the temperature reached 700 o C. The XRD result indicated that 15 phase-pure Co 2 P can be obtained at temperatures of above 700 o C. For the sake of comparison, Table 1 summarizes the phase structures of the samples obtained in this study. It was clear from Table 1 that pure MoP and Co 2 P can be obtained by 25 reduction of their corresponding precursors in DME at above 700 o C. In the case of Ni phosphide, reduction temperature was the key factor in the synthesis.…”
Section: Sample Characterizationsmentioning
confidence: 94%
“…27 It was suggested that the surface concentration of Ni 12 P 5 species on N-800 sample was too low to be detected by XPS. The result appeared to be 15 reasonable because only a small amount of Ni 12 P 5 phase was identified by XRD pattern of N-800 and this phase was also oxidized more readily than Ni 2 P phase in the passivation process. 39 Finally, the morphology and element composition of the as- 25 prepared metal phosphides (M-800, N-800 and C-800) were investigated.…”
Section: Sample Characterizationsmentioning
confidence: 95%
See 3 more Smart Citations